Thermal properties of big bluestem as affected by ecotype and planting location along the precipitation gradient of the Great Plains. - Zhang, Ke; Johnson, Loretta; Nelson, Richard; Yuan, Wenqiao; Pei, Zhijian J.; Sun, Xiuzhi S.; Wang, Donghai (My University, 2014)
The objective of this research was to study the effect of ecotype and planting location on thermal properties of big bluestem. Three big bluestem ecotypes (CKS, EKS, ILL) and a cultivar (KAW) were harvested in 2010 from four locations (Colby, Hays, and Manhattan, KS; and Carbondale, IL) and were evaluated for their specific heat, thermal conductivity, thermal stability, HHV (high heating value), and proximate contents. All populations revealed a large variation in specific heat (2.35-2.62 kJ/kg/K), thermal conductivity (77.85-99.06 x 10³ W/m/K), thermogravimetric analysis as weight loss during the heating process (71-73%), and HHV (17.64-18.67 MJ/kg). Specific heat of the big bluestem was significantly affected by planting location, ecotype, and interaction between location and ecotype. Planting location had stronger influence on specific heat than ecotype. Specific heat increased as temperature increased, and a linear correlation model for specific heat prediction was developed as a function of temperature. Ecotype, planting location, and the interaction of ecotype and planting location did not have a significant effect on thermal conductivity; however, density and particle size showed a completely opposite relationship on thermal conductivity. Both planting location and ecotype significantly affected HHV. Among all environmental factors, potential evapotranspiration had the most significant effect on thermal properties.
Keywords: Big bluestem; Ecotype; Environment; Thermal properties; Proximate contents